Tillandsia oliveirae (Bromeliaceae): a new species from an inselberg in Bahia, Brazil - Souza, Everton Hilo De; Leodegario, Marcio De Melo; Aona, Lidyanne Yuriko Saleme; Souza, Fernanda Vidigal Duarte; Leme, Elton M. C. (Phytotaxa, 2021)
The authors describe, discuss, and illustrate Tillandsia oliveirae, a new species from the inselbergs of the Caatinga biome in the municipality of Itatim, Bahia, Brazil. The new species is similar to T. hofackeri, differing by morphological characters such as larger size of the plant, longer peduncle, more laxly arranged leaves, which are more numerous, and whitish petals. It is an endemic species with a restricted area of distribution, being considered critically endangered (CR) due to illegal extractivism, specifically for regional and international trade.